International Technical-Scientific Cooperation in the Construction of Atmospheric Monitoring Networks. The Case of Bogotá (1960-2016) - Ángel Macías, Mauricio Alberto (2019)
Networks for air quality monitoring in cities have been positioned as useful technology to monitor and intervene on the danger posed by air pollution. The need to carry out global atmospheric monitoring has been based on the importance of this environmental problem to public health, especially after the second post war period. Monitoring technology appeared in Latin America in the 1960s, at a time when air pollution was not a major problem in the region. Even so, atmospheric surveillance was initiated, mediated by economic and political interests in the international power relations characteristic of this period. This article takes as a case study the city of Bogota, to explain how the unbalanced power relations between first and third world countries, and then between developed and developing countries, led to the creation of scientific technical systems and networks of atmospheric monitoring. These were at first more problematic than useful, but with the passage of time they became very important for the sanitary and environmental surveillance of the territory.